Analisis Kebutuhan Teknis Stakeholder Pada Produk Kursi Roda Manual Menggunakan Zachman Framework - Meilinda Ayundyahrini; S. Suprapto; Fakhrina Fahma; Wahyudi Soetopo; Eko Pujiyanto (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2019)
Most wheelchairs circulating in Indonesian market are imported from China at affordable prices, but do not fufill the ISO 7176 series standards. SNI 09-4663-1998 about wheelchair is one of medical devices standard. The standard is considered do not covers the quality and user safety, while wheelchair technology is transform rapidly. Mapping and analyzing gap between stakeholder need and SNI 09-4663-1998 is expected to be input of standard review to improve the competitiveness of products. This research using the Zachman Framework approach following FACTS steps. Data collection uses the observation, in-depth interviews and Focus Group Discussion. Data analysis using Inter Rater Reliability (IRR) which to measure the level of agreement of respondents. The results showed that stakeholder technical needs included 7 parameters: stability, maneuverability, mobility, dimensions, strength, durability, and product information. SNI 09-4663-1998 only includes the product strength parameters through a drop test so that the standard needs to be reviewed.